PEMANFAATAN MICRO INFLUENCER SEBAGAI PERTIMBANGAN KONSUMEN DALAM MEMILIH KULINER KAKI LIMA - Handaruwati, Indah; Dewi, Adhita Maharani (Jurnal Industri Kreatif dan Kewirausahaan, 2023)
The pandemic has forced business actors to innovate a lot, from products to services. This effort is focused on behavior changes that occur in society. Business actors must be good at reading what consumers need and ensure the right marketing strategy to get the right target. With all the regulatory limitations to prevent the spread of Covid 19, business actors are implementing new strategies to keep marketing their products running. Utilization of Influencers allows businesses to capture changes in consumer behavior directly. This concept not only helps business continuity in a pandemic, but also has the potential to create a shift towards the necessary changes going forward. The results of the study show the role of micro influencers for 40 respondents who become informants to act as their reference when consumers are choosing street food places. Respondents can confirm the cleanliness of the place, service, price when viewing the show and reading comments about the show. Impressions and content created by micro influencers influence thoughts and decisions about a place to eat.